2018
DOI: 10.1016/j.jinf.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of invasive aspergillosis in hematological malignancy patients: Performance of cytokines, Asp LFD, and Aspergillus PCR in same day blood and bronchoalveolar lavage samples

Abstract: High serum IL-8 levels were highly specific, and when combined with either the BALF Aspergillus-specific LFD, or BALF Aspergillus PCR also highly sensitive for diagnosis of IA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 39 publications
8
104
0
Order By: Relevance
“…11 In pediatric recipients with IPA, GM is measurable in peripheral blood. 11 In pediatric recipients with IPA, GM is measurable in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…11 In pediatric recipients with IPA, GM is measurable in peripheral blood. 11 In pediatric recipients with IPA, GM is measurable in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of other, non‐culture‐based methods for the detection of Aspergillus has gained traction over recent years, such that current proposals for the second revision of the EORTC/MSG definitions for IMI include consideration of Aspergillus PCR assays . PCR‐based assays have a wide range of reported sensitivities and have been suggested as a way to improve diagnostic accuracy when combined with other modalities, detect azole resistance and guide judicious use of preemptive antifungal treatment . Grancini et al suggested that BAL real‐time PCR, when performed in conjunction with routine BAL culture and GM, can have a NPV of 99% in immunocompromised patients, while Hoenigl et al reported 100% sensitivity and 98% specificity when combining PCR with GM.…”
Section: Discussionmentioning
confidence: 99%
“…Given the absence of widely accepted criteria for defining IPA in non‐neutropenic patients, studies on new diagnostic tests for IPA focus mostly on patients with underlying haematological malignancies, where broadly accepted classification criteria exist, while diagnostic studies in non‐neutropenic patients are scarce. Importantly, two novel point‐of‐care diagnostic tests, both European conformity (CE) marked for diagnosis of IPA in BALF, have recently become commercially available, but to date have been only validated in patients with underlying haematological malignancies .…”
Section: Introductionmentioning
confidence: 99%